\(=\dfrac{-5}{18}+\dfrac{-11}{36}=\dfrac{-10}{36}+\dfrac{-11}{36}=\dfrac{-21}{36}\)
\(=\dfrac{-10}{36}+\dfrac{-11}{36}\\ =\dfrac{-21}{36}\)
\(=\dfrac{-5}{18}+\dfrac{-11}{36}=\dfrac{-10}{36}+\dfrac{-11}{36}=\dfrac{-21}{36}\)
\(=\dfrac{-10}{36}+\dfrac{-11}{36}\\ =\dfrac{-21}{36}\)
\(\dfrac{-5}{18}\) + \(\dfrac{5}{9}\) - \(\dfrac{11}{36}\)
Quy đồng mẫu các phân số sau
\(a,\dfrac{5}{7}và\dfrac{9}{11}\) \(b,\dfrac{36}{42}và\dfrac{-12}{54}\)
\(c,\dfrac{-11}{30}và\dfrac{-17}{-40}\) \(d,\dfrac{36}{42}và\dfrac{-12}{36}\)
\(a,\dfrac{-6}{11}:\left(\dfrac{3}{5}:\dfrac{4}{11}\right)\) b,\(\dfrac{7}{12}+\dfrac{5}{12}:6-\dfrac{11}{36}\)
\(c,\left(\dfrac{4}{5}+\dfrac{1}{2}\right):\left(\dfrac{3}{13}-\dfrac{8}{13}\right)\) \(d,\left(\dfrac{2}{3}-\dfrac{1}{4}+\dfrac{5}{11}\right):\left(\dfrac{5}{12}-1-\dfrac{7}{11}\right)\)
Giúp mik nha:>>
\(\left[{}\begin{matrix}\\\end{matrix}\right.\dfrac{-5}{12}+\dfrac{6}{11}\) ] +[ \(\dfrac{7}{18}+\dfrac{5}{11}+\dfrac{5}{12}\)]
Tính Nhanh \(\dfrac{1}{2}-\dfrac{35}{-42}+2022-\dfrac{18}{36}-\dfrac{5}{6}\)
bài 1: tìm x
(\(\dfrac{5}{6}\) - x + \(\dfrac{7}{12}\)) : (\(\dfrac{11}{24}\) - \(\dfrac{1}{8}\)) = \(\dfrac{11}{36}\)
1)tính hợp lý: \(\dfrac{-5}{13}\times\dfrac{4}{11}+\dfrac{-5}{13}\div\dfrac{11}{7}+\dfrac{18}{13}\)
Bài 2: Tìm x, biết:
a) \(\left(x-\dfrac{5}{8}\right).\dfrac{5}{18}=-\dfrac{15}{36}\)
b) \(\left(x-\dfrac{1}{3}\right)=\dfrac{5}{6}\)
Tính hợp lý:
\(A=\dfrac{7}{12}+\dfrac{5}{12}:6-\dfrac{11}{36}\) \(B=\left(\dfrac{4}{5}+\dfrac{1}{2}\right):\left(\dfrac{3}{13}-\dfrac{8}{13}\right)\)
\(C=\left(\dfrac{2}{3}-\dfrac{1}{4}+\dfrac{5}{11}\right):\left(\dfrac{5}{12}+1-\dfrac{7}{11}\right)\)